Some southern African species of the genus Rhampsinitus Simon (Opiliones: Phalangiidae) - Starêga, Wojciech (Zootaxa, 2009)
Seven species of the genus Rhampsinitus Simon, 1879 from southern Africa are described or redescribed, among them Rhampsinitus flavobrunneus sp. nov. Some general remarks on the genus Rhampsinitus are given.